MODELING OF DENTAL PROSTHESES REMOVAL PROCESS BY MEANS OF VIBROIMPACT ULTRASONIC SYSTEM - M. G. Kiselev; A. P. Vertinskaya; D. A. Stepanenko (Наука и техника)
The results of experimental research on modeling dental prostheses removal process are given in the paper. It is determined on the basis of their analysis that the best conditions for detachment of prosthesis from a tooth body are provided in the case when a vibroiinpact mode of fracturing a cement layer used for crown fixation is realized.